2012
DOI: 10.1371/journal.pone.0030455
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Key Elements of FFAT-Like Motifs Identifies New Proteins That Potentially Bind VAP on the ER, Including Two AKAPs and FAPP2

Abstract: BackgroundTwo phenylalanines (FF) in an acidic tract (FFAT)-motifs were originally described as having seven elements: an acidic flanking region followed by 6 residues (EFFDA–E). Such motifs are found in several lipid transfer protein (LTP) families, and they interact with a protein on the cytosolic face of the ER called vesicle-associated membrane protein-associated protein (VAP). Mutation of which causes ER stress and motor neuron disease, making it important to determine which proteins bind VAP. Among other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 80 publications
3
121
0
Order By: Relevance
“…3A and 4E). Serine/threonine residues are frequently observed in the flanking region of FFAT motifs (21). Similar scenarios on the adjacent phosphorylation may occur in various FFAT motif-containing proteins to regulate their interaction with VAP.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…3A and 4E). Serine/threonine residues are frequently observed in the flanking region of FFAT motifs (21). Similar scenarios on the adjacent phosphorylation may occur in various FFAT motif-containing proteins to regulate their interaction with VAP.…”
Section: Discussionmentioning
confidence: 83%
“…Mikitova and Levine (21) showed that many proteins have FFAT-like motifs, which are similar, but with one or two suboptimal substitutions, to the canonical FFAT motifs (EFFDAXE). They further suggested that, although an FFATlike motif (TFFSAN) could not interact with VAP, the replacement of neutral amino acids to acidic amino acids in the motif (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2A) revealed the presence of a conserved FFAT-like motif at the C-terminal end of the MENTAL domain. Like other FFATlike motifs, this motif is centered on two aromatic residues with an adjacent tract of acidic amino acids (Mikitova and Levine, 2012). However, this motif differs from most other FFAT motifs as the acidic tract does not precede but follows the FF.…”
Section: Stard3 and Stard3nl Recruit The Er-resident Vap-a And Vap-b mentioning
confidence: 88%
“…The recently solved structure of the FAPP1 PH domain identified separate binding sites for binding of these two regulatory components (587, 885). An important common feature of all of these lipid-transfer proteins is the presence of a FFAT [two phenylalanines (FF) in an acidic tract] motif that provides an ER-association signal via interaction with ER-localized VAP (VAMP-associated) proteins (747,931,1049). Both the FFAT domain and the PH domain is essential for the lipid transfer (but not lipid cargo binding) functions of the proteins (564, 769, 1210), although the exact mechanism of how PtdIns4P regulates this process remains obscure (1262).…”
Section: B Golgimentioning
confidence: 99%